Analisis Perbandingan Tingkat Kesehatan Perbankan Studi Kasus pada Bank yang Termasuk dalam KBMI 3 (Panin, Permata, BSI) dan KBMI 4 (BCA, BRI, Mandiri) dengan Menggunakan Metode RGEC Periode 2019 – 2024 - Rindi Ayu Ristiani; Nurhafifah Amalina (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
The banking industry plays a strategic role in supporting the national economy as a financial intermediary institution that collects and distributes public funds. Following regulatory changes, the Financial Services Authority (OJK) has established a grouping of banks based on core capital, known as the Core Capital Bank Group (KBMI). KBMI 3 and KBMI 4 represent large-capital banks with broad business scopes and a crucial role in maintaining financial system stability. The 2019–2024 period is relevant for this study because it encompasses the regulatory transition from BUKU to KBMI. This study aims to analyze and compare the banking health of banks classified as KBMI 3 and KBMI 4 using the RGEC (Risk Profile, Good Corporate Governance, Earnings, and Capital) method during the 2019–2024 period. This study uses a quantitative descriptive approach with a comparative approach. The research sample was determined using a purposive sampling technique, including banks in KBMI 3 (Bank Panin, Bank BSI, and Bank Permata) and banks in KBMI 4 (Bank BRI, Bank Mandiri, and Bank BCA). The data used were secondary data obtained from the bank's annual financial reports. Data analysis was performed using two-group difference tests, namely the Independent Sample t-test and the Mann–Whitney U-test. The results showed a significant difference in the bank health level between KBMI 3 and KBMI 4 across all RGEC components. KBMI 4 had a better Risk Profile performance with a lower NPL ratio and a more stable LDR/FDR. In the GCG component, KBMI 4 demonstrated stronger governance implementation. In terms of Earnings, KBMI 4 had a higher level of profitability and better operational efficiency. Furthermore, the Capital component indicated that KBMI 4 had more stable and robust capital to support its business activities. Overall, this study concluded that KBMI 4 had a better level of bank health than KBMI 3 based on the RGEC method during the 2019–2024 period.